Does tax aggressiveness and capital structure affect firm performance? The moderating role of political connections - Sihono, Agus; Khairiyahtussolihah, Assa’adatul (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
This study examines how company performance affects tax aggressiveness, capital structure, and political connections. In addition, we also examine whether political connections moderate the effect of tax aggressiveness and firm performance, as well as capital structure and firm performance. Companies with aggressive tax strategies where they are politically connected perform better than vice versa. In addition, companies with larger external capital structures perform better when the company's boards are politically connected. In order to avoid the disadvantages of an aggressive tax strategy and a high external political model structure, the Company builds connections through the board to obtain projects from the government and avoid the risk of oversight by the authorities. Therefore, we suggest that regulators conduct inspections and supervision of companies that have political connections through the board to use unconstitutional methods to obtain projects from the Government or other benefits. In addition, we recommend that shareholders carefully carry out oversight in the context of overcoming agency problems in companies that are politically connected.